Evaluasi User Experience Aplikasi Google Meet Menggunakan Metode Usability Testing - Afzal Ziqri; Aditya Abi Riestianto; Ariq Cahya Wardhana (Journal ICTEE, 2022)
The pandemic forced almost everyone in the world to work from home. Almost all work is done online from home. With the Google Meet application, it can help make it easier for everyone to do their work even online. Since 2020 the Google Meet application has become a very popular application among the public. Google Meet is one of the many meeting applications that have been widely used by the public. To find out the usability value of the application, it is necessary to carry out a testing process through a usability test. SUS (System Usability Scale) is an evaluation that is used as a result of software usability.